Profile and Functional Prediction of Plasma Exosome-Derived CircRNAs From Acute Ischemic Stroke Patients - Yang, Jie; Hao, Junli; Lin, Yapeng; Guo, Yijia; Liao, Ke; Yang, Min; Cheng, Hang; Yang, Ming; Chen, Kejie (Frontiers in Genetics, 2022)
Stroke is one of the major causes of death and long-term disability, of which acute ischemic stroke (AIS) is the most common type. Although circRNA expression profiles of AIS patients have been reported to be significantly altered in blood and peripheral blood mononuclear cells, the role of exosome-contained circRNAs after AIS is still unknown. Plasma exosomes from ten AIS patients and ten controls were isolated, and through microarray and bioinformatics analysis, profile and putative function of circRNAs in the plasma exosomes were studied. A total of 198 circRNAs were differentially quantified (|log2 FoldChange|≥1.00, P<0.05) between AIS patients and controls. The levels of twelve candidate circRNAs were verified by qRT-PCR, and the quantities of ten of these circRNAs were consistent with the data of microarray. The functions of host genes of differentially quantified circRNAs, including RNA and protein process, focal adhesion and leukocyte transendothelial migration, were associated with the development of AIS. As miRNA sponge, differentially quantified circRNAs had the potential to regulate pathways related to AIS, like PI3K-Akt, AMPK and chemokine pathways. Of 198 differentially quantified circRNAs, 96 circRNAs possessing strong translational ability could affect cellular structure and activity, like focal adhesion, tight junction and endocytosis. Most differentially quantified circRNAs were predicted to bind to EIF4A3 and AGO2- two RNA binding proteins (RBPs)- and play a role in AIS. Moreover, four of ten circRNAs with verified levels by qRT-PCR (hsa_circ_0112036, hsa_circ_0066867, hsa_circ_0093708 and hsa_circ_0041685) were predicted to participate in processes of AIS, including PI3K-Akt, AMPK and chemokine pathways as well as endocytosis, and be potentially useful as diagnostic biomarkers for AIS. In conclusion, plasma exosome-derived circRNAs were significantly differentially quantified between AIS patients and controls, and participated in the occurrence and progression of AIS by sponging miRNA/RBPs or translating into proteins, indicating that circRNAs from plasma exosomes could be crucial molecules in the pathogenesis of AIS and promising candidates as diagnostic biomarkers and therapeutic targets for the condition.